(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the leaflet of the Ancient Mongolian Literature of the 13th century is analysed, which was composed during the period of the Mongolian conquest. It describes the opposition of two famous Mongolian leaders Chingiskhan and his friend Chzhamukhi. In the authorís opinion this work reflects social political and mental peculiarities of the Mongolian society best of all.